2022
DOI: 10.3390/toxics10110692
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Metal Exposures and Associations with Kidney Injury Biomarkers in Children

Abstract: Prenatal exposure to arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) may be nephrotoxic, yet limited studies have examined subclinical kidney injury biomarkers in children. We assessed whether metal exposure in the second trimester (2T), a crucial time of kidney development, is associated with altered urine kidney injury and function biomarkers in preadolescent children. Analyses included 494 children participating in a birth cohort study in Mexico City. Concentrations of As, Cd, and Pb were measured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Pronephros developmental frame is equivalent to about gestation period of 3-4 weeks in the human fetus. [86] In an epidemiological study, Politis et al [87] reported that prenatal metals exposure was related to kidney damage biomarkers in the urine of healthy children. Metal exposure during pregnancy may cause damage in the glomeruli or tubules in the offspring, which can impact the susceptibility to kidney damage in the later stages of life.…”
Section: Kidney-related Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pronephros developmental frame is equivalent to about gestation period of 3-4 weeks in the human fetus. [86] In an epidemiological study, Politis et al [87] reported that prenatal metals exposure was related to kidney damage biomarkers in the urine of healthy children. Metal exposure during pregnancy may cause damage in the glomeruli or tubules in the offspring, which can impact the susceptibility to kidney damage in the later stages of life.…”
Section: Kidney-related Disordersmentioning
confidence: 99%
“…Metal exposure during pregnancy may cause damage in the glomeruli or tubules in the offspring, which can impact the susceptibility to kidney damage in the later stages of life. [ 87 ] Jain reported synergistic effects of combined exposure to Pb, Cd, and Hg on the nephrotoxicity in a cross‐sectional study. For instance, when people were exposed to high amounts of two metals (Pb and Cd), their adjusted odds ratios (AORs) for unhealthy kidney function were more as compared to when they were exposed to only one metal (e.g., Pb).…”
Section: Multimetal Exposure‐associated Toxicity and Riskmentioning
confidence: 99%
“…MDC estimates (outdoor air pollutants) and biomarkers (metals/metalloids, pesticides, phthalates) in pregnant women were measured as previously detailed. [26][27][28][29] Briefly, we estimated daily concentrations in the Mexico City Metropolitan Area at 1-km 2 grids for two air pollutants (PM2.5, NO2) based on household location using validated spatiotemporal models and satellite information. [28,30] We then averaged concentrations for the three pregnancy trimesters.…”
Section: Exposures Assessmentmentioning
confidence: 99%
“…Should the kidneys not maintain the necessary changes, such as an increase in eGFR, spontaneous abortion has been recorded [ 1 ]. Furthermore, studies have described associations with preeclampsia in pregnant people with lead and cadmium exposures [ 12 , 13 ] and the development of kidney disease in the general population and in children with prenatal non-essential metal exposures [ 14 , 15 ]. Few studies have focused on the deleterious outcomes of toxic metals on the pregnant person’s kidney health instead of pregnancy outcomes [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%